2020
DOI: 10.1101/2020.04.12.038182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crosstalk between microRNA expression and DNA methylation drive the hormone-dependent phenotype of breast cancer

Abstract: Background:Abnormal DNA methylation is observed as an early event in breast carcinogenesis. However, how such alterations arise is still poorly understood. microRNAs (miRNAs) regulate gene expression at the post-transcriptional level and have been shown to play key roles in various biological processes. Here, we integrate miRNA expression and DNA methylation at CpGs to study how miRNAs may affect the breast cancer methylome and how DNA methylation may regulate miRNA expression. ResultsmiRNA expression and DNA … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…One such lncRNA was MEG3, which was shown to contribute to the development of cardiac fibrosis 38 . Further, the expression of the mature miRNAs hsa-miR-99a and hsa-miR-100 have previously been associated to fibroblasts in breast cancer 39 . We found that the corresponding miRNA precursor transcripts which themselves are lncRNAs were part of cluster 2 and were indeed expressed in fibroblasts of the tumor breast microenvironment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One such lncRNA was MEG3, which was shown to contribute to the development of cardiac fibrosis 38 . Further, the expression of the mature miRNAs hsa-miR-99a and hsa-miR-100 have previously been associated to fibroblasts in breast cancer 39 . We found that the corresponding miRNA precursor transcripts which themselves are lncRNAs were part of cluster 2 and were indeed expressed in fibroblasts of the tumor breast microenvironment.…”
Section: Discussionmentioning
confidence: 98%
“…The Oslo2 breast cancer cohort. The Oslo2 breast cancer cohort has been previously described 39,50,51 and is a consecutive study collecting material from breast cancer patients with primary operable disease at several hospitals in south-eastern Norway. Patients were included in the years 2006-2019.…”
Section: Methodsmentioning
confidence: 99%
“…mimQTL analysis R code is avai lab le f rom G it Hu b: h t t p s : / / g i t h u b . c o m / miriamragle/mimQTL.git [31].…”
Section: Statistical and Bioinformatical Analysismentioning
confidence: 99%
“…i) ChromHMM [37] enrichment of genomic regions mapped to the CpGs of cluster 1 and 2. j) Pathway enrichment using Enrichr [33] of genes mapped to the CpGs of cluster 2 according to the Illumina HumanMethy-lation450k array. k) Table of 273 Availability of data and materials mimQTL analysis R code is available from GitHub: https://github.com/ miriamragle/mimQTL.git [31]. This study utilizes publicly available data sets: The DNA methylation data of the Oslo2 cohort are available from the Gene Expression Omnibus (GEO) database with accession number GSE84207, https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE84207 [2].…”
Section: Supplementary Informationmentioning
confidence: 99%